(untitled) (Kindle, 2022)
Long-term complications are frequent in recovering COVID-19 cases. However, long-term complications of COVID-19 are currently unclear. If similar rate of long-term complications emerge following COVID-19, then we can expect a crashing wave of complications, which will have huge implication for treatment of the stretched healthcare resources in every country. A diverse group of symptoms, increasingly referred to as “Long COVID,” is also being reported in cases who did not need hospital treatment. These cases report a wide variety of manifestations, persisting for many months after acute infection. To date, most investigations on long COVID have been led by cases, and it proposes this is a frequent and disabling disease. More investigation informing clinical recommendations and our understanding of the mechanisms underlying this disease is urgently needed.